2022
DOI: 10.1177/08861099221099318
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Newcomer Women Who Experience Intimate Partner Violence and Their Children: Insights From Service Providers

Abstract: This qualitative study adds to research on the experiences of professionals who support newcomer women who have experienced intimate partner violence (IPV). Findings from seven focus groups with 32 service providers from newcomer-serving and domestic violence agencies in Saskatchewan, Canada, include newcomer survivors’ experiences of isolation, the impact of IPV on newcomer children, and challenges and opportunities for supporting newcomer women who have experienced IPV. Service providers described gaps in ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…Perpetrators of IPV maintained power and control by intentionally isolating survivors, and participants were also isolated due to their status as a newcomer and their limited English-language ability and social connections. This is consistent with findings from our study with service providers, who also reported that isolation was multi-layered and described newcomer victims who were isolated in their relationships, where isolation was used by partners to maintain power and control, and isolated living in new communities without the social and family connections that they had in their home countries (Giesbrecht et al, 2023). The present study also adds to the knowledge from previous studies with newcomer women in Eastern Canada who described their experiences of IPV, and of feeling alone in Canada without extended family or other supports, which was compounded by their husbands who intentionally isolated them and prevented them from forming new connections (Ahmad et al, 2009;Cottrell et al, 2009;Guruge & Humphreys, 2009;Mosher, 2009).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Perpetrators of IPV maintained power and control by intentionally isolating survivors, and participants were also isolated due to their status as a newcomer and their limited English-language ability and social connections. This is consistent with findings from our study with service providers, who also reported that isolation was multi-layered and described newcomer victims who were isolated in their relationships, where isolation was used by partners to maintain power and control, and isolated living in new communities without the social and family connections that they had in their home countries (Giesbrecht et al, 2023). The present study also adds to the knowledge from previous studies with newcomer women in Eastern Canada who described their experiences of IPV, and of feeling alone in Canada without extended family or other supports, which was compounded by their husbands who intentionally isolated them and prevented them from forming new connections (Ahmad et al, 2009;Cottrell et al, 2009;Guruge & Humphreys, 2009;Mosher, 2009).…”
Section: Discussionsupporting
confidence: 92%
“… 3. Results from the focus groups with service providers in Saskatchewan are reported in Giesbrecht et al (2023). An article reporting results relating to help-seeking from the interviews with newcomer survivors in Saskatchewan is forthcoming.…”
mentioning
confidence: 99%
“…These interventions have shown to be beneficial in reducing reduce peri-migratory traumas for women and children, especially those who have fled from violence in their home countries. However, there is a limited availability of mental health services specifically for newcomer children [43]. Most of the interventions focused on children make use of art or sand play, or target parents instead, in order to improve parenting techniques or improve child-parent relationships [17,34,36,37].…”
Section: Discussionmentioning
confidence: 99%
“…In the context of separation, for example, women’s priorities often shift to include: accessing adequate housing and creating economic stability [ 7 ]; supporting children and dealing with custody and access disputes [ 8 , 9 ]; managing chronic health concerns [ 10 ]; and accessing help from complex systems that are confusing and, at times, unresponsive [ 10 , 11 ]. The impact of these issues, and the challenges of dealing with them, are magnified for women who face structural inequities of poverty, stigma and/or discrimination, including Indigenous women [ 12 , 13 ], newcomers [ 14 ], and those living in underserved communities, including in rural settings [ 15 ]. In the context of chronic stress, women’s efforts to manage their lives in ways that support their recovery, safety, health and well-being may be undermined, at considerable cost to women, families, communities and society [ 16 ].…”
Section: Introductionmentioning
confidence: 99%